Apical root resorption of maxillary anterior teeth after orthodontic treatment of Class II division 1 occlusion with Roth appliance - Saad S Gasgoos (University of Mosul, College of Dentistry, 2004)
The aims of this study were to evaluate the effect of orthodontic treatment on root length (ratios of root length after / be-fore treatment) of the upper anterior teeth after correction of Class II division 1 incisal relation, to evaluate the time of treatment and its effect on root resorption and to show if there is any risk of root resorption in relation to sex.The sample was composed of 25 patients (15 females and 10 males) 15-25 years old age. All patients were treated with 22×30 slot brackets fixed stainless steel Roth system appliances after extraction of bilateral maxillary first premolars. The ca-nines were retracted individually along the base arch wire with power chain elastics that were changed every 1 week, then the four upper incisors were retracted with vertical loops.The results of periapical radiograph measurements before and after treatment indicated that there were a noticeable apical root resorption with blunted irregular apex after the completion of orthodontic treatment. The incisor roots were affected more than the canines. In addition, there were no gender differences in root resorption between males and females (except upper left lateral incisor). The mean treatment time from beginning to end of treatment and obtaining Class I incisal relation was 21.4 months.